Carbon nanotube self-assembly with lipids and detergent: a molecular dynamics study. - Wallace, E; Sansom, MS (2009)
The dispersion of carbon nanotubes (CNTs) in aqueous media is of potential importance in a number of biomedical applications. CNT solubilization has been achieved via the non-covalent adsorption of lipids and detergent onto the tube surface. We use coarse-grained molecular dynamics to study the self-assembly of CNTs with various amphiphiles, namely a bilayer-forming lipid, dipalmitoylphosphatidylcholine (DPPC), and two species of detergent, dihexanoylphosphatidylcholine (DHPC) and lysophosphatidylcholine (LPC). We find that for a low amphiphile/CNT ratio, DPPC, DHPC and LPC all wrap around the CNT. Upon increasing the number of amphiphiles, a transition in adsorption is observed: DPPC encapsulates the CNT within a cylindrical micelle, whilst both DHPC and LPC adsorb onto CNTs in hemimicelles. This study highlights differences in adsorption mechanism of bilayer-forming lipids and detergents on CNTs which may in the future be exploitable to enable enhancement of CNT solubilization whilst minimizing perturbation of cell membrane integrity.